Institute of Metals Division - Structure Dependent Chemical Activity Of Polycrystalline Cu3 Au–Experiments Relating To the Mechanism of Stress-Corrosion Cracking of Homogeneous Solid Solutions - Robert Bakish; William D. Robertson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1957)
AFTER more than fifty years of investigation and continuing failure in service, a satisfactory mechanism to explain stress corrosion cracking in homogeneous alloys is still lacking. The relative chemical activity of grain boundaries and adjacent grains, inferred from the boundary structure, has been used to explain intergranular cracking in a brass.' This concept is probably correct as a general hypothesis, but it requires much more extensive development in order to explain satisfactorily the observed phenomena. For example, the specific function of the solute in an alloy must be considered, because intergranular failure does not occur in pure metals,' which are structurally similar to homogeneous alloys. Also, in this connection, an inter crystalline fracture path in binary copper alloys can be changed to a transcrystalline path by relatively small ternary additions.' The fracture path in ß brass is predominantly transcrystalline,' in contrast with an inter crystalline path in a brass. Whether the two different fracture paths are the result of a difference in composition, crystal structure, or the state of long range order is unknown and cannot be determined with ß brass, because only the ordered state can be obtained at room temperature. The study of chemical activity at structural sites in the Cu-Zn system is restricted by the formation of opaque films in an ammonia environment in which stress corrosion cracking is generally observed. Furthermore, both components of the alloy are chemically active and the interpretation of observations is therefore relatively complicated. The Cu-Au system is a better choice for the purpose of studying structural factors. In particular, CuAu is very susceptible to cracking in ferric chloride and opaque films are not formed in this solution; it may be obtained in different states of long and short range order; and, finally, only copper is oxidized in dilute ferric chloride, which considerably simplifies the chemical problem. To provide information necessary for a more general explanation of stress corrosion cracking in homogeneous solid solutions, the following structural factors have been investigated in a Cu-Au alloy having a composition corresponding to Cu,Au: 1) the effect of long and short range order; 2) the structural sites from which copper is removed from the annealed and cold worked polycrystalline alloy; and 3) the effect of annealing time and temperature on structural reactions in the cold worked alloy. Experimental Procedure A Cu-Au alloy of nominal Cu3Au composition was cast from cathode copper and high purity gold and fabricated into sheet and wire. Chemical analysis for copper and gold indicated 48.92 wt pct Cu and 51.01 pct Au. Quantitative spectrographic analysis indicated 0.01 pct Ag, 0.002 pct Pd, 0.001 pct Pb, and 0.002 pct Fe, with traces of magnesium, silicon, and zinc. Presumably most of the remaining 0.055 pct corresponds to the limits of analytical precision. Heat treatments of wire and sheet were conducted in argon or vacuum. Wire specimens, 0.064 in. diam, were heated for 1 hr at 850 °C to establish a definite